A Concise History of Ancient Israel : From the Beginnings Through the Hellenistic Era - Schipper, Bernd U.; Lesley, Michael (University Park, PA : Penn State University Press, 2021)
The history of biblical Israel, as it is told in the Hebrew Bible, differs substantially from the history of ancient Israel as it can be reconstructed using ancient Near Eastern texts and archaeological evidence. In A Concise History of Ancient Israel, Bernd U. Schipper uses this evidence to present a critical revision of the history of Israel and Judah from the late second millennium BCE to the beginning of the Roman period. Considering archaeological material as well as biblical and extrabiblical texts, Schipper argues that the history of "Israel" in the preexilic period took place mostly in the hinterland of the Levant and should be understood in the context of the Neo-Assyrian expansion. He demonstrates that events in the exilic and postexilic periods also played out differently than they are recounted in the biblical books of Ezra and Nehemiah. In contrast to previous scholarship, which focused heavily on Israel's origins and the monarchic period, Schipper's history gives equal attention to the Persian and early Hellenistic periods, providing confirmation that a wide variety of forms of YHWH religion existed in the Persian period and persisted into the Hellenistic age.Original and innovative, this brief history provides a new outline of the historical development of ancient Israel that will appeal to students, scholars, and lay readers who desire a concise overview.
Frontmatter -- Contents -- List of Illustrations -- Preface -- List of Abbreviations -- Chronology -- Chapter 1 Introduction -- Chapter 2 The Origins of Israel and Its Early History (1208-926/925 BCE) -- Chapter 3 Israel and Judah from 926/925 to the Conquest of Samaria in 722/720 BCE -- Chapter 4 The Judean Monarchy from 722/720 to the Conquest of Jerusalem in 587/586 BCE -- Chapter 5 The Persian Period (550-333 BCE) -- Chapter 6 The Hellenistic Period (333-64/63 BCE) -- Archaeological Periods -- Maps -- Bibliography -- Index of Authors -- Index of Place and Personal Names -- Index of Scripture -- Index of Other Ancient Sources
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mai 2021).
JSTOR
Keywords: Bible. -- History of Biblical events; Jews -- History -- To 70 A.D.; Palestine -- History -- To 70 A.D.; HISTORY / Middle East / Israel & Palestine